Triglyceride Levels on Electronic Cigarette Vapers in Palangka Raya - Suratno Suratno; Dwi Purbayanti; Arnino Adhy Satya (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2018)
The electronic cigarette (e-cigarette) is one of the Nicotine Replacement Therapy uses electricity from battery power to deliver nicotine as aerosols. Nicotine can stimulate secretion of catecholamine lead to increase secretion of hepatic triglycerides to the blood vessels. This study aimed to asses the triglyceride levels of electronic cigarette smokers (also known as vapers) on a vaporizer community in Pahandut, Palangka Raya, Central Kalimantan. The cross-sectional design was carried out to asses triglyceride levels on 29 electronic cigarette users. Triglyceride assay was determined by an automated photometric technique using Photometers (5010 V5+ Robert Riele). This study found that mostly e-cigarette user considered normal triglyceride level as 75.9% with average triglyceride level 100.6 mg/dL, 13.8% considered borderline-high triglyceride level with average triglyceride level 180.8 mg/dL, and only 10.3% considered high triglyceride level with average triglyceride level 293.0 mg/dL.